Respuesta :
Answer:
The correct simplification of the given expression  [tex]tan(-x){\times}cos(-x)[/tex] is [tex]-sinx[/tex].
Step-by-step explanation:
The given expression is:
[tex]tan(-x){\times}cos(-x)[/tex]
Now, simplifying the above given expression, we get
=[tex]\frac{sin(-x)}{cos(-x)}{\times}cos(-x)[/tex] (because [tex]tanx=\frac{sinx}{cosx}}[/tex])
=[tex]sin(-x)[/tex]
Also, we know that [tex]sin({-\theta})=-sin{\theta}[/tex], tehrefore teh expression becomes
=[tex]-sinx[/tex]
Hence, the correct simplification of the given expression  [tex]tan(-x){\times}cos(-x)[/tex] is [tex]-sinx[/tex].